Length of stay and determinants of early discharge after facility-based childbirth in Cameroon: analysis of the 2018 Demographic and Health Survey - Jovanny Tsuala Fouogue; Aline Semaan; Tom Smekens; Louise-Tina Day; Veronique Filippi; Matsui Mitsuaki; Florent Ymele Fouelifack; Bruno Kenfack; Jeanne Hortence Fouedjio; Thérèse Delvaux; Lenka Beňová (BMC, 2023)
Abstract Background A minimum length of stay following facility birth is a prerequisite for women and newborns to receive the recommended monitoring and package of postnatal care. The first postnatal care guidelines in Cameroon were issued in 1998 but adherence to minimum length of stay has not been assessed thus far. The objective of this study was to estimate the average length of stay and identify determinants of early discharge after facility birth. Methods We analyzed the Cameroon 2018 Demographic and Health Survey. We included 4,567 women who had a live birth in a heath facility between 2013 and 2018. We calculated their median length of stay in hours by mode of birth and the proportion discharged early (length of stay < 24 h after vaginal birth or < 5 days after caesarean section). We assessed the association between sociodemographic, context-related, facility-related, obstetric and need-related factors and early discharge using bivariate and multivariable logistic regression. Results The median length of stay (inter quartile range) was 36 (9-84) hours after vaginal birth (n = 4,290) and 252 (132-300) hours after caesarean section (n = 277). We found that 28.8% of all women who gave birth in health facilities were discharged too early (29.7% of women with vaginal birth and 15.1% after a caesarean section). Factors which significantly predicted early discharge in multivariable regression were: maternal age < 20 years (compared to 20-29 years, aOR: 1.44; 95%CI 1.13-1.82), unemployment (aOR: 0.78; 95%CI: 0.63-0.96), non-Christian religions (aOR: 1.65; 95CI: 1.21-2.24), and region of residence-Northern zone aOR:9.95 (95%CI:6.53-15.17) and Forest zone aOR:2.51 (95%CI:1.79-3.53) compared to the country's capital cities (Douala or Yaounde). None of the obstetric characteristics was associated with early discharge. Conclusions More than 1 in 4 women who gave birth in facilities in Cameroon were discharged too early; this mostly affected women following vaginal birth. The reasons leading to lack of adherence to postnatal care guidelines should be better understood and addressed to reduce preventable complications and provide better support to women and newborns during this critical period.